Analysis Of Coliform Bacteria Content In Tofu Soaking Water Based On Length Of Tofu Soaking For The Presence Of Coliform Based On The Most Probable Number (MPN) Test - Erlinda Erlinda; Samingan Samingan; Iswadi Iswadi; Wardiah Wardiah; Wiwit Artika (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2023)
Presence of Coliform bacteria is affected by the quality of water contaminated with feces, so the tofu soaking water used must meet the requirements of good clean water so that the quality of tofu is protected from contamination by pathogenic bacteria. This study aims to determine the effect of tofu soaking time on the presence of Coliform bacteria. The approach used is a descriptive approach to the type of experimental research. Sampling used the Purposive Sampling method, consisting of 4 samples, namely samples of well water, PDAM, 24-hour immersion water and 48-hour immersion water. Analysis of data on the presence of Coliform bacteria using the MPN test. The MPN test showed positive results with the Coliform bacteria content exceeding the standard MPN value threshold, which was 1,100 colonies/mL. Based on the research results, soaking time of tofu has an effect on the presence of Coliform bacteria. Results of the Gram stain as a follow-up test proved that the Gram-negative bacteria of the Coliform group contaminating the tofu soaking water. Based on the results of the study it was concluded that the water used for soaking tofu at the tofu factory in Jaya Baru District, Banda Aceh City did not meet the requirements because it was contaminated with Coliform bacteria.Keywords: Tofu, soaking water, Coliform bacteria Keberadaan bakteri Coliform dipengaruhi oleh kualitas air yang tercemar oleh tinja, air rendaman tahu yang digunakan harus memenuhi syarat air bersih agar kualitas tahu terhindar dari cemaran bakteri patogen. Penelitian ini bertujuan untuk mengetahui pengaruh lama perendaman tahu terhadap keberadaan bakteri Coliform. Pendekatan yang digunakan pendekatan deskriptif dengan jenis penelitian eksperimen. Pengambilan sampel menggunakan metode Purposive Sampling, terdiri dari 4 sampel yaitu sampel air sumur, PDAM, air rendaman 24 jam dan air rendaman 48 jam. Analisis data keberadaan bakteri Coliform menggunakan uji MPN. Uji MPN menunjukkan hasil positif dengan kandungan bakteri Coliform melebihi ambang batas standar nilai MPN yaitu 1.100 koloni/mL. Berdasarkan hasil penelitian lama perendaman tahu berpengaruh terhadap keberadaan bakteri Coliform. Hasil pewarnaan Gram sebagai uji lanjut, membuktikan yang mengontaminasi air rendaman tahu merupakan bakteri Gram negatif kelompok Coliform. Berdasarkan hasil penelitian disimpulkan bahwa air yang digunakan untuk perendaman tahu di pabrik tahu Kecamatan Jaya Baru Kota Banda Aceh tidak memenuhi syarat karena tercemar oleh bakteri Coliform.Kata kunci: Tahu, air rendaman, bakteri Coliform.